A community based screening of gestational diabetes mellitus within 16 weeks of pregnancy: a study from Mysuru district, Karnataka - Sinha, Abhishek Kumar; B., Madhu; M. R., Narayana Murthy (International Journal Of Community Medicine And Public Health, 2018)
Background: Gestational diabetes mellitus is defined as carbohydrate intolerance with onset/recognition during pregnancy where maternal and perinatal complications are increased. Aged care facilities in rural areas reports disparity in the management of gestational diabetes as compared with urban counter parts. As a need to address this, study conducted with objective to estimate prevalence of gestational diabetes mellitus within 16 weeks of gestation for GDM by oral glucose challenges test. Methods: Antenatal mothers attending primary health centers within 16 weeks of gestation were screened for GDM. Two hours, venous samples were calculated for estimation of blood glucose level. Plasma glucose level of >140mg/dl was considered as OGTT positive. Results: Among 301 patients examined 11 mothers had OGTT positive results. GDM was seen in 3.7% of Mothers. GDM is found significantly associated with increasing age (p=0.01, t=2.52, mean difference 2.54 CI 0.5-4.5), weight (p=0.04, t=2.24, mean difference 10.8 CI 0.11-21.5), and BMI (p<0.01, t=2.97, mean difference 3.6 CI 1.2-6). GDM was seen more in multigravida (P=0.01). Statistically significant association of GDM was found with mean systolic (p<0.01, t=2.62, mean difference 8.08 CI 2.01-14.14) and diastolic blood pressure (P<0.01, t=3.44, mean difference 7.87 CI 3.38-12.36). A multiple regression shows these variables statistically significantly predicted GDM, F (5, 295)= 7, p<0.001, R2=0.106. Conclusions: GDM is statistically associated with increasing age, increasing weight, BMI and multiple gravida in pregnancy. It is recommended to screen for GDM within the 1st trimester & follow up needed to prevent further complications.